2014
DOI: 10.1103/physrevlett.113.248101
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Selection in Growing Tubular Tissues

Abstract: Tubular organs display a wide variety of surface morphologies including circumferential and longitudinal folds, square and hexagonal undulations, and finger-type protrusions. Surface morphology is closely correlated to tissue function and serves as a clinical indicator for physiological and pathological conditions, but the regulators of surface morphology remain poorly understood. Here, we explore the role of geometry and elasticity on the formation of surface patterns. We establish morphological phase diagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 33 publications
5
91
0
Order By: Relevance
“…During development, the initially smooth outer cortex grows at a faster rate than the inner white matter core [14]. Differential growth gives rise to residual stresses that induce a mechanical instability, which results in surface buckling [15,16]. The stress patterns associated with differential growth theories agree well with physical stress measurements in the developing ferret brain [17].…”
Section: Motivationmentioning
confidence: 78%
“…During development, the initially smooth outer cortex grows at a faster rate than the inner white matter core [14]. Differential growth gives rise to residual stresses that induce a mechanical instability, which results in surface buckling [15,16]. The stress patterns associated with differential growth theories agree well with physical stress measurements in the developing ferret brain [17].…”
Section: Motivationmentioning
confidence: 78%
“…With growing attention to the concept of mechanical deformation to explain a variety of morphogenetic events (Ciarletta et al, 2014;Drasdo, 2000;Savin et al, 2011;Takigawa-Imamura et al, 2015;Varner et al, 2015), branching formation based on physical buckling (Varner et al, 2015) and local apical constriction (Kim et al, 2013) have been proposed as mechanisms of bud formation. In our model, apical constriction was assumed to occur globally within the cyst, and uniformly sized buds emerge spontaneously without pre-patterning of protruding regions.…”
mentioning
confidence: 99%
“…For example, it has been shown that both elastic properties and the geometry of the growing layers are key factors determining the pattern selection and the emergence of several functional structures on the epithelium of gastro-intestinal tissues [102,23]. In the following, we define a morpho-elastic model of a hyperelastic soft tissue made of two flat layers growing under a spatial constraint.…”
Section: Pattern Formation In a Growing Bilayer Under Lateral Constraintmentioning
confidence: 99%